6th International Conference on Technologies & Business Models for Circular Economy: Conference Proceedings - Marina Bajić; Potrč, Sanja; Bogataj, Miloš; Kravanja, Zdravko; Novak Pintarič, Zorka (2024)
The 6th International Conference on Technologies & Business Models for Circular Economy (TBMCE) was organized by the Faculty of Chemistry and Chemical Engineering of the University of Maribor in cooperation with Strategic Research and Innovation Partnership – Networks for the transition into circular economy (SRIP – Circular economy), managed by the Chamber of Commerce and Industry of the Štajerska. The conference was held in Portorož, Slovenia, at the Grand Hotel Bernardin from September 6th to September 8th, 2023. TBMCE 2023 was devoted to presentations of circular economy concepts, technologies and methodologies that contribute to the shift of business entities and society as a whole to a more responsible, circular management of resources. The conference program included a round table Standardization for circular economy – more secure and less complicated closing of material loops, 6 panel discussions, 1 plenary and 3 keynote lectures, oral and poster presentations. The event was under the patronage of Ministry of the Economy, Tourism and Sport and Ministry of Cohesion and Regional Development. The Netherlands joined us as a partner country.
Keywords: circular economy; sustainable development; processes and technologies; circular business models; research and development